Anti-inflammatory effects of water extract of Taraxacum mongolicum hand.-Mazz on lipopolysaccharide-induced inflammation in acute lung injury by suppressing PI3K/Akt/mTOR signaling pathway. (20th June 2015) - Ma, Chunhua; Zhu, Lingpeng; Wang, Jing; He, He; Chang, Xiayun; Gao, Jin; Shumin, Wang; Yan, Tianhua
Abstract: Ethnopharmacological relevance: Taraxacum mongolicum Hand .- Mazz is a famous medicinal plant in China, has been listed in the Pharmacopoeia of the People׳s Republic of China and used to treat infection, fever, upper respiratory tract infection, pneumonia, and other infectious diseases. This study aims to evaluate the possible mechanisms responsible for the anti-inflammation effects of water extract of T. mongolicum Hand .- Mazz (WETMHM) on lipopolysaccharide (LPS)-induced inflammatory in acute lung injury. Materials and methods: Female BALB/c mice were randomly divided into five groups with 10 mice in each group: (1) control group (saline), (2) LPS group, (3) LPS+dexamethasone (LPS+Dex, 2 mg/kg, administered by gavage), (4) LPS+WETMHM (5 g/kg, administered by gavage), (5) LPS+WETMHM (10 g/kg, administered by gavage). The cell counting in the bronchoalveolar lavage fluid (BALF) was measured. The animal lung edema degree was evaluated by wet/dry weight (W/D) ratio. The superoxidase dismutase (SOD) activity and myeloperoxidase (MPO) activity were assayed by SOD and MPO kits, respectively. The levels of inflammation mediators including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6 were assayed by an enzyme-linked immunosorbent assay method. Pathological changes of lung tissues were observed by hematoxylin and eosin (HE) staining. The levels of P-PI3K, PI3K, P-Akt, Akt, P-mTOR and mTOR were measured by Western blotting. Results: The data showed that treatment with the WETMHM inhibited LPS-induced inflammation: (1) WETMHM attenuated inflammation cell numbers in the BALF, (2) decreased protein levels of lung PI3K/Akt/mTOR, and (3) improved SOD activity and (4) inhibited MPO activity; (5) histological studies demonstrated that WETMHM substantially inhibited LPS-induced neutrophils in lung tissue. Conclusion: The results indicated that the WETMHM had a protective effect on LPS-induced ALI in mice. Graphical abstract: